Diversity in Tuber Characteristics of Local Cultivars of Yam Bean (Pachyrhizus erosus) in Indonesia - Ayda Krisnawati; Sutrisno Sutrisno; Mochammad Muchlish Adie (Biosaintifika: Journal of Biology & Biology Education, 2018)
Yam bean is legume with tuberous root originated from the semiarid tropics of Central America, and has been widely spread in several regions in Indonesia. Research on characterization of tuber yam bean was conducted in Kendalpayak Research Station (Malang, Indonesia) from May to October 2016. A total of 73 local yam bean cultivars originated from eight provinces were characterized based on their tuber characteristics. The sensory evaluation was also conducted to evaluate the tuber sweetness, fiber intensity, and texture crunchiness. The average tuber weight was 455.2 g/plant, with the average tuber length and width were 10.78 cm and 8.17 cm, respectively. The ratio of tuber length and width was 1.42, indicates that yam bean tuber in Indonesia tend to be in spherical shape. The average tuber water content was 83.87% (wet basis), showed that the water content was quite high. Based on cluster analysis, 74 local cultivars of yam bean were grouped into five clusters. The tuber weight varied among cultivars and become the distinguishing factor between local cultivars. Local variety of yam beans in Indonesia tend to have sweet taste and crunchy texture. So far, the study on characterization of tuber diversity in Indonesian local cultivar of yam bean is still limited. Thus, these results provide important information to optimize the tuber yam utilization as industrial raw materials.